A cluster randomised controlled trial to assess the effectiveness of a multi-strategy sustainability intervention on teachers' sustained implementation of classroom physical activity breaks (energisers): study protocol - Nicole Nathan; Alix Hall; Adam Shoesmith; Adrian E. Bauman; Belinda Peden; Bernadette Duggan; Carly Gardner; Cassandra Lane; Christophe Lecathelinais; Christopher Oldmeadow; Craig Duncan; Daniel Groombridge; et al. (BMC, 2023)
Abstract Background Governments internationally have invested hugely in the implementation and scale-up of school-based physical activity interventions, but have little evidence of how to best sustain these interventions once active implementation support ceases. This study will assess the effectiveness of a multi-strategy sustainability intervention on classroom teachers' sustainment of energisers (short 3-5 min physical activity breaks during class-time) scheduled across the school day from baseline to 12 and 24-month follow-up. Methods A cluster randomised controlled trial will be conducted in 50 primary schools within the Hunter New England, Illawarra Shoalhaven, Murrumbidgee and Northern New South Wales (NSW) Local Health Districts of NSW Australia. Schools will be randomly allocated to receive either usual support or the multi-strategy sustainability intervention that includes: centralised technical assistance from a trained project officer; formal commitment and mandated change obtained from school principals; training in-school champions; reminders for teachers; educational materials provided to teachers; capturing and sharing local knowledge; and engagement of parents, carers and the wider school community. The primary trial outcome will be measured via a teacher logbook to determine the between-group difference in the change in mean minutes of energisers scheduled across the school day at 12 and 24-month follow-up compared to baseline. Analyses will be performed using an intention to treat framework. Linear mixed models will be used to assess intervention effects on the primary outcome at both follow-up periods. Discussion This study will be one of the first randomised controlled trials to examine the impact of a multi-strategy sustainability intervention to support schools' sustainment of a physical activity intervention. The proposed research will generate new evidence needed for the partnering organisations to protect their considerable investments to date in physical activity promotion in this setting and will provide seminal evidence for the field globally. Trial registration ACTRN12620000372987 version 1 registered 17th March 2020. Version 3 (current version) updated 4th August 2023.